2016
DOI: 10.18632/oncotarget.11807
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock components RORα and Bmal1 mediate the anti-proliferative effect of MLN4924 in osteosarcoma cells

Abstract: The anticancer small molecule MLN4924, a Nedd8-activating enzyme (NAE) inhibitor, triggers cell-cycle arrest, apoptosis, and senescence in cancer cells. In this study, we demonstrate that MLN4924 suppresses osteosarcoma cell proliferation by inducing G2/M cell cycle arrest and apoptosis. Our results indicate that MLN4924 stabilizes the retinoid orphan nuclear receptor alpha (RORα) by decreasing its ubiquitination. RNA interference of RORα attenuates the anti-proliferative effect of MLN4924 in U2OS osteosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…SH-SY5Y cells treated with SR1078 exhibited an increase in the expression of RORα target genes (37). MLN4924 may stabilize RORα to suppress proliferation and induce apoptosis in osteosarcoma cells (38). Pantoprazole inhibited the proliferation, self-renewal, and chemoresistance of GC stem cells via the EMT/β-catenin pathway (39); reversed the aggressiveness and EMT marker expression of SGC7901/ADR cells; and suppressed the Wnt/β-catenin pathway (40).…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells treated with SR1078 exhibited an increase in the expression of RORα target genes (37). MLN4924 may stabilize RORα to suppress proliferation and induce apoptosis in osteosarcoma cells (38). Pantoprazole inhibited the proliferation, self-renewal, and chemoresistance of GC stem cells via the EMT/β-catenin pathway (39); reversed the aggressiveness and EMT marker expression of SGC7901/ADR cells; and suppressed the Wnt/β-catenin pathway (40).…”
Section: Discussionmentioning
confidence: 99%
“…1D). The sensitivity of cancer cells to MLN4924 appeared to be associated with their NAE1 levels, which was consistent with previous reports (15)(16)(17).…”
Section: Mln4924 Inhibits Proliferation Of CML Cells With Nae1 Overexsupporting
confidence: 92%
“…MLN4924 treatment induces apoptosis, DNA damage, and cell-cycle arrest in multiple types of solid and hematopoietic malignant cells (14). Pevonedistat is currently under phase I clinical trials (15,16). Whether neddylation inhibition by MLN4924 induces apoptosis in T315I-BCR-ABL þ cells is elusive.…”
Section: Introductionmentioning
confidence: 99%
“…BMAL1 is a key circadian clock gene that regulates tissue homoeostasis, metabolism and ageing, and it is the only single clock gene knockout in which the experimental animals lose rhythmic behavioural activities 13 . The dysregulation of BMAL1 has been documented in various tumours, such as haematological malignancies 14 , lung cancer 15 , osteosarcoma 16 and PC 17 19 . We previously demonstrated that decreased BMAL1 expression in PC suppresses the p53 pathway and significantly enhances tumour growth 19 .…”
Section: Introductionmentioning
confidence: 99%